Clinical, Endocrine and Genetic spectrums of Mucopolysaccharidoses type VI in Duhok city, Kurdistan Region, Iraq: Clinical, Endocrine & Genetic spectrums of Mucopolysaccharidoses - Haleem, Azad A. (Cellular and Molecular Biology, 2022)
Mucopolysaccharidoses type VI is a rare disorder and establishing the diagnosis requires assays that are unavailable in a routine care setting. There is an increased risk of considerable diagnostic delay and missing patients due to incorrect diagnosis. The present study was conducted to determine the socio-demographic characteristics, clinical manifestations, and anthropometric parameters of patients with MPS type VI. Patients' enzyme levels and genetic profiles were also examined. The present study included a total of 16 patients who had been diagnosed as MPS type VI and were referred to Hivi Pediatric Hospital in Duhok, Kurdistan Region, Iraq, till the time period of March 2022. Diagnoses were made in all the patients by analyzing the enzyme level. Moreover, a genetic study was performed to confirm the diagnosis. From each of the patients, a blood sample was taken to determine the hematological parameters. Among the study participants, 9 were males and 7 were females. The mean age of the patients was 6.81±4.99 years and the age at diagnosis was 21.13±15.19 months. All of them presented with a course facial features, 75% had short stature, 87.5% had corneal clouding, 12.5% had glaucoma, 68.75% had poor vision, 18.75% of them had optic nerve disease, 56.25% had otitis media, 56.25% had poor hearing, 68.75% had a history of recurrent sinusitis, 50% had an enlarged tongue, and 75% had abnormal teeth. Approximately 56.25% of the patients presented with sleep apnea, 37.5% had obstructive and restrictive airway disease, none of the patients had cardiac arrhythmia, 37.5% had cardiomyopathy, 31.25% had abdominal hepatosplenomegaly, 81.25% had skeletal abnormalities, all of the patients had normal intelligence, 9 (56.25%) had a past medical history of other systemic illness and 7 (43.75%) had a past history of surgery. Out of the total number of patients, 13 patients had c.962T>C (p.(Leu321Pro)) mutation, one patient had c.585T>A (p.(ASP195Glu)) mutation, one patient had c.[585T>A];[753C>G] (Asp195 Glu];[Tyr251 Ter]), and one patient had c.{288C>A];[962T>C] (p.[Ser96Arg];[Leu321Pro]) mutations. Due to the rarity in prevalence, early detection of the said disorder is critical; early treatment may result in improved outcomes, which may have potential significance for newborn screening.